2007
DOI: 10.14411/fp.2007.031
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasitic mites of the genus Endotrombicula Ewing, 1931 (Acari: Prostigmata: Parasitengona: Trombiculidae) from African and Madagascan anurans, with description of a new species

Abstract: Abstract.A sample of over 6,000 specimens of frogs belonging to about 120 species of all families occurring in West Africa and Madagascar were screened for parasitic mites. Three species of Endotrombicula Ewing, 1931 were found in representatives of two African and two Madagascan frog families. All Trombiculidae found in African frogs belonged to Endotrombicula pillersi (Sambon, 1928), whereas in Madagascar E. madagascariensis (Sambon, 1928) and E. ptychadenae sp. n. were sampled. These three species are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
(20 reference statements)
1
28
0
Order By: Relevance
“…The prevalence of mites varies between amphibian species (Alvarado‐Rybak et al., ; Biolé et al., ), as well as between habitats (Attademo et al., ). The genus Endotrombicula, a member of the family Trombiculidae, is known to parasitize African and Malagasy leaf‐litter frogs (Hyland, ; Krantz & Walter, ; Wohltmann, du Preez, Rödel, Köhler, & Vences, ). Only the Endotrombicula larvae are parasitic.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of mites varies between amphibian species (Alvarado‐Rybak et al., ; Biolé et al., ), as well as between habitats (Attademo et al., ). The genus Endotrombicula, a member of the family Trombiculidae, is known to parasitize African and Malagasy leaf‐litter frogs (Hyland, ; Krantz & Walter, ; Wohltmann, du Preez, Rödel, Köhler, & Vences, ). Only the Endotrombicula larvae are parasitic.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable data on the coordinates of collection localities obtained with the use of satellite navigation systems occur in publications on chiggers since 2005 only (Brown 2006b(Brown , 2008Wohltmann et al 2007). All coordinates in older works are not reliable, because authors never reported a method for obtaining this information (by navigation instruments, by topographic maps, or with a reference bookin the case of coordinates of populated places).…”
Section: Information Resourcesmentioning
confidence: 99%
“…femoralis) were found in the same microhabitat. Several specimens from Marojejy had pinkish mites (probably of the genus Endotrombicula; see Wohltmann et al 2007) embedded within translucent whitish pustules on the skin of their fingers, toes, and bodies. Nothing is known about the reproduction of this species, but the calling sites suggest an association with lotic water.…”
Section: Distributionmentioning
confidence: 99%